Imagem e automação – Considerações sobre ‘Hesitant Hand’ de Pakui Hardware - Mateus, João Ricardo Antunes (CEM – Cultura, Espaço & Memória, 2020)
The prominence of the technological has a concrete impact on information tools, auxiliary to the perception of the real. This article focuses on the implications of this aspect in the field of contemporary artistic production, through Hesitant Hand, a work by Pakui Hardware. Hesitant Hand is used as a starting point for a reflection on automation and image, which in the case of Hesitant Hand, is informed by the automation process. This article tries to explain the implication of the image in the presented case study, by juxtaposing the automation process and the images of Hesitant Hand. Pakui Hardware’s work presents us with images that focus on the semantics of the image itself and portrays an ecosystem in flux. This paper argues that Hesitant Hand presents three distinct set of images and contributes to the ongoing debate concerned with the image by displaying images that are plural and polymorphic.